Cancer specific up-regulated lactate genes associated with immunotherapy resistance in a pan-cancer analysis - Shuiting Fu; Jiachen Xu; Chunming Wang; Cheng Zhang; Chengcheng Li; Wenchuan Xie; Guoqiang Wang; Xin Zhu; Yuyan Xu; Yaohong Wen; Jingyuan Pei; Jun Yang; et al. (Heliyon)
Background: Although the lactate pathway has been reported to lead to immune escape through the inhibition of effector T cells, the cancer-intrinsic lactate signature has not been identified, and the immunotherapeutic efficacy and potential mechanism of the lactate signature are still unclear. Methods: We defined a pan-cancer up-lactate score by comparing malignant tissues and normal tissues in the TCGA cohort. The immunotherapeutic efficacy was evaluated in non-small cell lung cancer (NSCLC), metastatic renal cancer (mRCC), bladder cancer (BLCA) and melanoma cohorts. The cancer cell-intrinsic mechanism to immune checkpoint inhibitors (ICIs) resistance was measured using single cell sequencing (scRNA-seq) data. Pathway activation was evaluated in the TCGA cohort and CPTAC cohort with transcriptomics and proteomics. The co-occurrence of up-lactate signature and mTOR signaling was determined by spatial transcriptomics of the tissue samples. Immunotherapy resistance and pathway regulation were validated in the in-house NSCLC cohort. Results: Patients with the high up-lactate scores had significantly short overall survival (OS) than those with the low up-lactate scores (p < 0.001) across multiple types of cancers. The up-regulated lactate signature exhibited higher expression in the malignant cells compared with stromal cells and immune cells in multiple scRNA-seq datasets. A high up-lactate score was associated with poor OS in NSCLC, mRCC, BLCA and melanoma patients who received anti-PD(L)1 antibody. The up-lactate score was higher in the responders of cancer cells, but not in immune cells and stromal cells compared with the non-responders (p < 0.05). Moreover, up-lactate score was positively correlated with mTOR signaling across multiple cancers. In patients with NSCLC who received anti-PD-1 antibody, higher up-lactate scores were associated with significantly shorter PFS compared to lower up-lactate scores (p < 0.001). Additionally, the up-lactate score was associated with cold tumor, and was positively correlated with mTOR signaling. Conclusion: Collectively, we defined a pan-cancer up-lactate signature, which is a feature of malignant cells and is associated with ICIs resistance. This reveals a coherent program with prognostic and predictive value that may be therapeutically targeted.